2007
DOI: 10.1007/s10856-007-3326-9
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of porous apatite granules from calcium phosphate cement

Abstract: A versatile method for preparing spherical, micro-and macroporous (micro: 2-10 and macro: 150-550 lm pores), carbonated apatitic calcium phosphate (Ap-CaP) granules (2-4 mm in size) was developed by using NaCl crystals as the porogen. The entire granule production was performed between 21 and 37°C. A CaP cement powder, comprising a-Ca 3 (PO 4 ) 2 (61 wt.%), CaH-PO 4 (26%), CaCO 3 (10%) and precipitated hydroxyapatite, Ca 10 (PO 4 ) 6 (OH) 2 (3%), was dry mixed with NaCl crystals varying in size from 420 lm to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 85 publications
1
61
0
Order By: Relevance
“…26 According to Bohner and Baumgart, the in vivo resorption rate of porous granules can be predicted to be much faster than in dense blocks or prismatic objects made out of the same material. 27 Moreover, Tas 25 demonstrated that the same calcium phosphate granules as we used in our study are able to almost fully absorb citrated blood or fluid PRP prior to their implantation, which is based on a high wicking ability of the granules. This may be the reason for a more extensive and longer absorption of the PRP by the granules in our study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…26 According to Bohner and Baumgart, the in vivo resorption rate of porous granules can be predicted to be much faster than in dense blocks or prismatic objects made out of the same material. 27 Moreover, Tas 25 demonstrated that the same calcium phosphate granules as we used in our study are able to almost fully absorb citrated blood or fluid PRP prior to their implantation, which is based on a high wicking ability of the granules. This may be the reason for a more extensive and longer absorption of the PRP by the granules in our study.…”
Section: Discussionmentioning
confidence: 66%
“…First of all, the granules are comprised of carbonated, calcium-deficient, apatitic CaP and exhibit a closer resemblance to human bone than stochiometric HA or TCP ceramics. 25 In addition, the interconnected network of micro-and macro-pores promote and allow bony ingrowth within the threedimensional geometry of the scaffold. 26 According to Bohner and Baumgart, the in vivo resorption rate of porous granules can be predicted to be much faster than in dense blocks or prismatic objects made out of the same material.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, clinical breakthroughs are made daily in the medical and dental sciences; these include, among others, the enhancement of the injectable (Bohner and Baroud, 2005;Habib et al, 2008), biocompatibility, and self-setting properties of CPC paste by organic matter (Maruyama and Ito, 1996) as well as the development of novel apatite blocks (Tas, 2008). The injectability of CPC grout is also one of the most important factors in its application to natural soils and rocks with minute cracks.…”
Section: Application Of Knowledge In and Collaboration With Medical Amentioning
confidence: 99%
“…The need of bioceramics for minimal invasive surgery has induced the development of a concept of self-setting formulations consisting of only calcium orthophosphates to be applied as injectable and/or mouldable bone substitutes [156,400,401,418,475,[514][515][516][517][518][519][520][521][522]. In addition, there are reinforced formulations, which, in a certain sense, might be defined as calcium orthophosphate concretes [516].…”
Section: Cements and Concretesmentioning
confidence: 99%